Multisectoral governance for health: challenges in implementing a total ban on chrysotile asbestos in Thailand. (10th October 2018) - Kanchanachitra, Churnrurtai; Tangcharoensathien, Viroj; Patcharanarumol, Walaiporn; Posayanonda, Tipicha
Abstract : Introduction: Interest in multisectoral governance for health has grown in recent years in response to the limitations of government-centric policy formulation and implementation. This study describes multisectoral governance associated with policy formulation and implementation of a total ban on chrysotile asbestos in Thailand. Methods: Qualitative methods were applied, including analysis of related literature and media, and in-depth interviews with key informants. Consent was obtained for interview and tape recording; protection of confidentiality was fully assured. Results: An agenda on total ban of chrysotile asbestos was proposed to the National Health Assembly, where a resolution was adopted in 2010. The resolution was endorsed by the Cabinet in 2011, which mandated the Ministry of Industry to implement the ban immediately. There was uneven interest and ownership by stakeholders in the policy formulation process. Long delays in implementation have been observed. Furthermore, while the policy is likely to affect relatively few industries there has been misinformation on the safe use of chrysotile, and delaying tactics and pressure from major chrysotile-exporting countries. Conclusion: The National Health Assembly is a useful platform for policy formulation on complex policy issues requiring multisectoral action. However, policy implementation is challenging due to lack of clear policy across sectors. Success in protecting people's health requires participatory policy-making and effective governance of multisectoral action throughout implementation. The Assembly is not designed to enforce implementation, especially when power and authority lie with state actors, but monitoring and public reporting would be powerful tools to drive this agenda.